Intubation outcomes and practice trends during the initial New York SARS‐COV‐19 surge at an academic, level 1 trauma, urban emergency department. Issue 6 (24th November 2021) - D'Amore, Jason; Meigher, Stephen; Patterson, Elizabeth; Sanapala, Sowmya; Tarr, Michael; Leisman, Dan; Jones, Michael; Moskovitz, Joshua B; Offenbacher, Joseph; Sperling, Jeremy
Abstract: Objectives: The goal of this study was to describe outcomes and associated characteristics of patients who were intubated during the initial (3/2020‐4/2020) New York City surge of the severe acute respiratory syndrome coronavirus 2 (COVID‐19) pandemic, during which time we were confronted by an unknown and unprecedented respiratory distress syndrome with extremely high degrees of morbidity and mortality. Our secondary aim was to analyze our physician's rapidly evolving approaches to COVID‐19 airway management. Methods: A retrospective cohort analysis of all patients intubated at two emergency departments (EDs) for COVID‐19 suspected respiratory failure. In addition, a survey was done to analyze clinician airway management trends and attitudes as they evolved during that period. Results: Ninety‐five patients met inclusion criteria for the study. Primary outcomes looked at the spectrum of mortality outcomes ranging from died on arrival (DOA) to the ED, died in the ED (DED), died an inpatient (DIH), and survival to discharge. Overall mortalitywas 71.6% with an average age of 62.7 years. Female sex, as a demographic, was associated with higher rates of survival to discharge at 42.3% when compared to males at 23.2% ( P < 0.001). Mean age was 70.8 years DOA, 65.6 years DED, 62.9 years DIH, and 60.0 years for survivors ( P = 0.0037). Initial lactate levels were 8.15 mmol/L DED, 3.56 mmol/L DIH, and 2.61 mmol/L survivors ( P < 0.0001). Initial creatinine levels were 3.38 mg/dL DED, 1.94 mg/dL DIH, and 1.77 mg/dL survivors ( P = 0.0073). D‐dimer levels were 7520.5 ng/mL DED, 5932.4 ng/mL DIH, and 1133.9 ng/mL survivors ( P = 0.0045). Physician survey respondents reported high levels (69%) of laryngeal edema and prolonged post intubation hypoxia (>50% of time) and >80% remained concerned for their safety. There was a dramatic shift from early (73% of time) to late intubation strategies (67% of time) or non‐invasive approaches (28% of time) as the first surge of the pandemic evolved. Conclusion: Our findings demonstrate that several demographic, clinical and laboratory parameters correlated with mortality in our cohort of patients intubated during the initial phase of the COVID‐19 pandemic. These included male sex, advanced age, high levels of initial lactic acidosis, elevated D‐dimer, and chronic kidney disease/acute kidney injury. In contrast, presenting respiratory characteristics were not correlated with mortality. In addition, our findings demonstrate that physician attitudes and strategies related to COVID‐19 airway management evolved significantly and rapidly over the initial phase of the pandemic.